1999
DOI: 10.1515/ncrs-1999-0121
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of trans-bis[2-hydroxy-5-methyl-phenonethanoneoximato- N,O]nickel(II), C18H20N2NiO4

Abstract: C18H20N2NÌO4, triclinic, P\ (No. 2), a = 6.296(5) Â, b = 8.204(7) À, c = 8.653(8) Â, α = 71.92(6)°, β = 80.61(7)°, γ= 83.84(6)°, V=418.4À 3 ,Z= 1, pm= 1.536 g-crrT 3 , Rg{F) = 0.045, RV/(F 1 ) = 0.115, 7=293 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…For general background to the applications of 2-hydroxyaryloxime complexes in extractive metallurgy and biology, see: Keeney et al (1984); Elo & Lumme (1985); Chaudhuri (2003); Milios et al (2007). For related structures, see: Hatzidimitriou et al (1997); Voutsas et al (1999).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For general background to the applications of 2-hydroxyaryloxime complexes in extractive metallurgy and biology, see: Keeney et al (1984); Elo & Lumme (1985); Chaudhuri (2003); Milios et al (2007). For related structures, see: Hatzidimitriou et al (1997); Voutsas et al (1999).…”
Section: Related Literaturementioning
confidence: 99%
“…E65, m1305 [https://doi.org/10.1107/S1600536809039257] (Chaudhuri, 2003;Elo & Lumme, 1985;Keeney et al, 1984;Milios et al, 2007). (Hatzidimitriou et al, 1997), and bis[2-(5-methyl-1-(hydroxyimino)ethyl)phenolato]nickel (Voutsas et al, 1999), have been reported. As a continuation of these studies, the structure of the title complex, (I), is described herein.…”
Section: Supporting Informationmentioning
confidence: 99%